The Effectiveness of Sharia Ruqyah for Children with Mental Disorders: A Case Study - Muhammad Amin; Mukarom (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Children's mental health is an important aspect of individual development that influences social, emotional, and academic life. Objectives: This study aims to analyze the effectiveness of ruqyah syar'iyyah therapy in treating mental disorders in school-age children. Methods: The method used was qualitative research with a case study approach at the Ruqyah Syar'iyyah Center Clinic in Malang (RSC-M). Data collection techniques were carried out through observation, interviews, and documentation of 10 child participants aged 12-18 years. Data analysis used qualitative analysis developed by Matthew B. Miles by extracting data to identify subthemes and main themes. Results: The research results show that ruqyah syar'iyyah therapy has a positive impact on children's psychological well-being, such as reducing anxiety, providing emotional stability, and improving self-control. The therapy stages include preparation, implementation, and post-therapy reinforcement. Conclusions: Ruqyah syar'iyyah has been proven effective as a complementary therapy in helping children recover from mental disorders with a spiritual and psychological approach